Management of giant fibromatous epulis: a case report - Husni Mubarak; Irfan Rasul; Nurwahida (Makassar Dental Journal PDGI Makassar, 2020)
Background: Epulis fibromatosa is a hyperplastic reaction of fibrous connective tissue due to chronic stimulation or irritation, such as sharp parts of the retained root. The mass was pedunculated, pale pink in color, solid consistency, the boundary was firm, and was not easy to bleed with no pain. Aim:Discuss the management of giant fibromatous epulis by excision. Case: A 49-years-old man came to Dental Hospital of Hasanuddin University, complained of gums that had enlarged and disturbed while chewing so that the patient had difficulty to close his mouth. The masses appeared since 3 years ago, initially small and gradually grew to the size 10x5x7 cm, solid consistency, well-defined, not easy to bleed, and not painful. The mass has been treated by excision and removal of tooth 37 in general anesthesia. Discussion: Patient was temporarily diagnosed with suspected fibromatous epulis and the presence of retained root, probably caused by chronic irritation from sharp parts of retained root. Fibrous connective tissue hyperplasia is a benign soft tissue tumor as the response to local irritants. Conclusion: The excision of fibromatous epulis was carried out to remove the mass and eliminating the predisposed factor.